1996
DOI: 10.1021/es9505154
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Lead Speciation in Contaminated Soils by EXAFS Spectroscopy

Abstract: Direct determination of the chemical form of trace metals in soils still remains a challenge for instrumental analytical techniques. This paper examines the potential of EXAFS spectroscopy to speciate and quantify the form of trace metals in the solid fraction of soil materials using lead as a case study. Three soils contaminated by different sorts of industrial activities, including the synthesis of lead organometallics for gasoline antiknocks, Pb-Zn smelting, and recycling of lead acid battery, were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
249
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(272 citation statements)
references
References 48 publications
15
249
2
6
Order By: Relevance
“…The coordination number for root samples was particularly low compared to that of Pb(CH 3 COO) 2 Á3H 2 O because of the high structure disorder of the Pb coordination shells in root samples. Similar observations for Pb-O coordination have been reported for organic macromolecules such as humic acids, fulvic acids or salicylate in soils (e.g., Manceau et al 1996), for lichen cells exudates such as oxalate and parietinic acid (Sarret et al 1998), and for lignocellulosic biomaterial (Dupont et al 2002).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The coordination number for root samples was particularly low compared to that of Pb(CH 3 COO) 2 Á3H 2 O because of the high structure disorder of the Pb coordination shells in root samples. Similar observations for Pb-O coordination have been reported for organic macromolecules such as humic acids, fulvic acids or salicylate in soils (e.g., Manceau et al 1996), for lichen cells exudates such as oxalate and parietinic acid (Sarret et al 1998), and for lignocellulosic biomaterial (Dupont et al 2002).…”
Section: Discussionsupporting
confidence: 83%
“…Being one of the most frequently encountered metal contaminants in many agricultural and industrial areas, the environmental fate of Pb and its uptake by plants has been the subject of much research (Manceau et al 1996;Wu et al 1999). Because of its limited solubility due to the formation of insoluble precipitates, bioavailable levels of Pb in soils are generally low compared to other heavy metals, thus making it difficult to apply phytoremediation techniques to Pb-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the hydroxyl group of 2,4,6-TCP permits orientational interactions with H-bonding sites on soil organic matter and clay surfaces (Boyd, 1982). However, lead also can bind to these groups (Manceau et al, 1996). The overlapping of adsorption sites implies that lead may suppress the sorption of 2,4,6-TCP on these groups of organic matter and clay minerals.…”
Section: Effect Of Ph On Sorptionmentioning
confidence: 99%
“…At low concentrations, lead is adsorbed at the specific adsorption sites. Manceau et al (1996) observed that lead adsorbed in soils tends to form inner-sphere complexes, in which lead is coordinated with hydroxyl functional moieties from soil particles (clay mineral and soil organic matter) (Xia et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, scanning electron microscopy and energy-dispersive X-ray and Xray adsorption fine structure (XAFS) analyses have been used to characterize the reaction product and forms of lead in contaminated soils (33,44,45).…”
Section: Reducing Exposurementioning
confidence: 99%